Study of hygroscopic expansion of anode readout boards of gaseous detectors based on FR4. (9th March 2021) - Bortfeldt, J.; Dubinin, F.; Iengo, P.; Samarati, J.; Zhukov, K.
Abstract: The problem of hygroscopic expansion of FR4 based large-size PCBs is discussed using the example of Micromegas detector. The readout electrodes of the detector located on the anode printed circuit board assumed to have precise dimensions. During the production and delivery process, the readout PCB is exposed to different temperature and humidity conditions. As a result, the PCB size differs from the nominal one at the moment of assembly of the detector. The problem appears to be relevant for any other large-size gaseous detectors with the readout structure based on FR4. The swelling of two test PCB samples during water absorption is studied. The size of the samples is 650× 500× 0.5 mm 3 . Both samples have copper strips on one side. The second side is naked on sample 1 and fully covered with a copper layer on sample 2. The elongation of the samples from dry conditions to 50% RH is measured. The influence of the copper layers on the absorption rate and the value of equilibrium elongation is discussed. It is shown that elongation of sample 1 follows the Fick's law while the absorption process in sample 2 is more complicated. The coefficient of linear hygroscopic expansion of sample 1 is measured and discussed.